External engagement and the academic heartland: The case of a regionally-embedded university. (3rd June 2016) - Pinheiro, Rómulo; Normann, Roger; Johnsen, Hans Christian Garmann
Abstract: This paper explores patterns of external engagement at the department level, a rather neglected aspect in the existing literature. The case used is that of a mid-sized comprehensive university located in the south of Norway. The data emanate from a survey questionnaire administered in the spring of 2011. Respondents were asked questions pertaining to three main areas: the types of engagement, the nature of the engagement, and the perceived benefits accruing to the academic units involved (internal) and to society (external). The results reveal significant variations within and across departments, with the pattern of such variations being more random than was expected. We explain the key findings and reflect on the implications for future scholarship in the area, demonstrating the limitations associated with the 'one-size-fits-all' approach to the role of the university in society and the economy.